2016
DOI: 10.4283/jmag.2016.21.2.239
|View full text |Cite
|
Sign up to set email alerts
|

A Rotating Flux Pump Employing a Magnetic Circuit and a Stabilized Coated Conductor HTS Stator

Abstract: High temperature superconductor (HTS) magnet systems usually employ metal current leads which bridge between the cryogenic environment and room temperature. Such current leads are the dominant heat load for these magnet systems due to a combination of electrical resistance and heat conduction. HTS flux pumps enable large currents to be injected into a HTS magnet circuit without this heat load. We present results from an axialtype HTS mechanically rotating flux pump which employs a ferromagnetic circuit and a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…From figures 6 and 7 a linear dependence of V average (I) is observed over a wide range of impressed currents. This trend is widely confirmed in experiments [4][5][6][7][8], and in the considered case applies for an operating current approximately within the interval from −100 A to +100 A (see figure 7). Thus, within this linear interval, the following expression can be introduced for the average terminal voltage…”
Section: V(t I)supporting
confidence: 77%
See 3 more Smart Citations
“…From figures 6 and 7 a linear dependence of V average (I) is observed over a wide range of impressed currents. This trend is widely confirmed in experiments [4][5][6][7][8], and in the considered case applies for an operating current approximately within the interval from −100 A to +100 A (see figure 7). Thus, within this linear interval, the following expression can be introduced for the average terminal voltage…”
Section: V(t I)supporting
confidence: 77%
“…The average motional electromotive force produced by the PM onto the elements (thin wires) of the discretization during one rotation cycle is shown in figure 3. This is the voltage impressed by the voltage sources of the FEM-based equivalent circuit of figure 2, corresponding to terms u h in equation (6). They apply both for the current driven operation (figure 2(a)) and for the RL load (figure 2(b)).…”
Section: Numerical Results Discussion and Empirical Equivalent Circui...mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the fact that the magnetic field distribution in HTS tapes would be changed by the FM materials [45], we applied a piece of permalloy slice in the experiments, aiming at studying the influence it may bring. We have used an oscilloscope to monitor the open-circuit voltage waveform, as is shown in figure 7, from which we found that there are only tiny differences between the waveforms when the tape was immersed in the LN 2 and was put at room temperature, but leads to a totally different result [46].…”
Section: Open-circuit Voltagementioning
confidence: 99%